BITTERNESS AND RECOGNITION: ROOM FOR OTHERS IN THE NOVELS OF STEPH CHA - WILLEMS, Brian Daniel (International Journal of Korean Humanities and Social Sciences, 2021)
The novels of Steph Cha posit two key characteristics for openness toward others: bitterness and recognition. The thesis of this paper is that both characteristics must be present together in order for openness to occur. Cha’s Juniper Song detective series (2013-15), as well as her stand-alone novel Your House Will Pay (2019), foreground the role that bitterness and recognition play in an openness of Korean-Americans to other American people of color. Following the work of Jacques Rancière and Axel Honneth, bitterness is seen as a characteristic that keeps recognition from falling into the oppressive traps of one group only recognizing the pre-established modes of identity of another. Cha’s novels insist on moments of bitterness within scenes of recognition, thus showing how both characteristics, together, form an essential way for a positive openness to another to be possible. Other Korean-American authors discussed include Cathy Park Hong, Caroline Kim, and Theresa Hak Kyung Cha.